Pemantauan Indeks Massa Tubuh dalam Pencegahan Obesitas pada Masyarakat Kelurahan Kessilampe Kota Kendari - Irma Yunawati; Wa Ode Salma; Nurnashriana Nurnashriana; Ayu Anisa Putri Arifin; Yuliah Dani; Nazhifa Nahda Aremanita; Waode Hety Dirahayu; Risma Septiyani Syahrir; Yuanita Adinda (Jurnal Anestesi, 2025)
Obesity is a risk factor for degenerative diseases in developing countries. This is due to changes in people's lifestyles, including physical activity and eating patterns, influenced by the socio-economic development of urban and rural communities. This activity aims to determine the cut-off point for obese nutritional status based on the Body Mass Index (BMI) indicator. The study seeks to evaluate the nutritional and health status of the community in Kessilampe Village, Kendari City, by measuring Body Mass Index (BMI) and waist circumference. A total of 50 respondents participated in this activity, with the majority being women (86%). The research method used a descriptive design with a cross-sectional approach. Data collection was conducted through measurements of height (HT), weight (WT), and body mass index (BMI) on 50 adults, consisting of 7 males and 23 females.The measurement results indicated that 58% of respondents were in the normal weight category, while 26% were overweight and 16% were classified as obese. Waist circumference measurements also revealed that 44% of respondents had a waist circumference between 81-90 cm, indicating health risks associated with obesity.